Religiosity of Rular Muslim Communities (Study of The Role Darul Qudwah Fondation in Penusupan, Tegal) - Nisa Aulia Ningsih; Agus Riyadi; Sulistio Sulistio; Syahrul Ganda Sukmaya (Prosperity: Journal of Society and Empowerment, 2023)
The study was intended to analyze the role of the Darul Qudwah Foundation in updating rural Muslim religiosity, especially in the village of Penusupan. The issue regarding religious edification is interesting to consider because changing people's behavior is a condition that is expected of most people, especially rural Muslims. Nevertheless, the reality is that not all villagers will readily accept the cultivation that will lead to good, especially in communities that still have a disease of the heart and trust in the occult. This type of research is a descriptive qualitative with a phenomenon approach. Data collection techniques using observation, interviews and documentation. Research shows the role of the Darul Qudwah Foundation as an enabler, which is the creation of Taklim's council and Islamic faith facilities. The broker is the broker of civil conflict between religious and otherwise. The expert on relationships and making a point of gratitude. The agent of development is a change in people's behavior through the gift of granaries, a tolerance program.